THE IMPORTANCE OF ENGLISH COMPETENCIES TOWARD THE EMPLOYERS AT TOURISM DEPARTMENT IN SOUTH SULAWESI (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research is about the role of English competence for employees at Tourism Department of South Sulawesi. This study aims to find out the role of English and employees respond to English competence in South Sulawesi. The researcher used a qualitative descriptive method. The data collection technique used is to determine the subject, questionnaires, interviews, data analysis and conclusions. In this study it can be concluded that 62.85% of respondents "agreed" that the role of English is very important for the South Sulawesi Tourism Office and employees. and employee responses to English competence that they need English to develop and introduce culture and tourism in South Sulawesi to various countries in Asia and Europe such as Malaysia, the Netherlands and Spain, so that English can be said to be a second language at Tourism Department of  South Sulawesi.